The influence of service quality, price, and promotion on GO-FOOD user loyalty - Cahya, Lyvia; Afiliasi, Hendratmoko (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This research aims to analyze the impact of service quality, price, and promotion on Go-Food users in Jakarta, Indonesia. A total of 150 respondents from Jakarta participated in this study, providing data through a distributed questionnaire. Utilizing IBM SPSS Ver. 25, the author conducted statistical tests on the collected data. Results revealed that service quality (X1) and price (X2) had no significant impact on customer loyalty. However, the promotion variable was found to significantly influence customer loyalty among Go-Food users in Jakarta. This suggests the need for Go-Food to reassess its service quality and pricing strategies. Additionally, this research provides valuable insights for GoTo investors in their decision-making processes. Future studies could explore other variables affecting Go-Food user loyalty in Jakarta, thereby contributing to the theoretical foundation of online food delivery services